Long-Term Exit-Site Gentamicin Prophylaxis and Gentamicin Resistance in a Peritoneal Dialysis Program. Issue 4 (July 2016) - Chen, Shan Shan; Sheth, Heena; Piraino, Beth; Bender, Filitsa
Background: Daily gentamicin cream exit-site prophylaxis reduces peritoneal dialysis (PD)-related gram-negative infections. However, there is a concern about the potential for increasing gentamicin resistance with the long-term use of prophylactic gentamicin. This study evaluated the incidence of gentamicin-resistant PD-related infections over more than 2 decades. Methods: Study data on prevalent PD patients were retrieved from a prospectively maintained institutional review board (IRB)-approved PD registry at a single center from January 1, 1991, to December 31, 2000, and January 1, 2004, to December 31, 2013. The rates of gram-negative infections, fungal infections and those infections with organisms resistant to gentamicin were examined for the 2 periods. Period 1 from 1991 to 2000 when S. aureus prophylaxis consisted initially of oral rifampin to treat nasal carriage with S. aureus, and was then daily exit-site mupirocin ointment for all PD patients, was compared to the period from 2004 to 2013 when daily exit-site gentamicin cream was prescribed as prophylaxis (Period 2). Results: The study included a total of 444 PD patients (265 and 179 in Period 1 and Period 2, respectively). No significant difference was noted in demographics between the 2 periods except race. The gram-negative exit-site infection rates for Period 1 and Period 2 were 0.109 versus 0.027 ( p < 0.0001). Gram-negative peritonitis rates were similar. There were 3 episodes of gentamicin-resistant infections in each period. Fungal infections remained consistently low. Conclusion: Despite a decade of exit-site gentamicin prophylaxis, gentamicin-resistant PD-related infections and fungal infections remained very low and similar to the prior period.